Towards an extended resource theory of marital power: parental education and household decision-making in rural China - CHENG Cheng, (Institutional Knowledge at Singapore Management University, 2023)
Existing literature on the resource theory of marital power has focused on the relative resources of spouses and overlooked the resource contributions of spouses’ extended families. We propose an extended resource theory that considers how the comparative resources of a couple’s natal families are directly associated with marital power, net of the comparative resources of the couple. Using data from the China Panel Family Studies, we examine how the relative education of a couple’s respective parents affects the wife’s decision-making power, net of the relative education of the couple. Results suggest that the higher the wife’s parental education relative to her husband’s parental education, the more likely she is to have the final say over household financial decisions. Our study underscores the importance of situating the study of marital power in the extended family context and highlights the significance of social origins and intergenerational exchanges for marital power.